Violence, primary school learning and development in the Cape Flats township of Mitchells Plain: a case study of exposure to violence and its implications for children's' learning and development - Kampfer, Judine Pearl (University of Cape Town, 2020)
This case study focused on the ways in which their exposure to violence impacts on primary school children's learning and their cognitive and emotional development in two primary schools in the Cape Flats Township of Mitchell's Plain. The research aimed to explore the extent to which exposure to violence impacts not only on these learners' learning and development but also the various ways in which these children act-out their violent experiences. The fieldwork focused on how the exposure to violence in the household and community influences/affects classroom learning, in particular, learners' oral and written exercises, as well as the quality of their relationships with teachers and other learners. The theoretical framework for this research is based on Vygotsky's Social Developmental theory. This theory assisted me in my investigation and helped me to understand the consequences of exposure to violence for both learning and cognitive and emotional development within a social, or socio-cultural context. I used Bronfenbrenner's ecological models to explain the impact exposure to violence has on human development and cognitive growth within an ecological system. The research approach made use of a qualitative case study of two primary schools, each situated in a different socio-economic area of Mitchell's Plain. The data was collected from participant observations, focus group interviews, and document analysis of learners' writings and drawings. The research found the sample of learners from both schools to have been affected both mentally/cognitively and emotionally by the violence in the area, and that this had caused these learners to lose focus and had certainly affected their academic performance. A key point that emerged was that the sample of learners participating in the study were struggling to create quality relationships with their teachers and peers. The research showed that, causally related to this, children in the study who had been directly or indirectly exposed to violence displayed a lack of trust and confidence in others, and that this often led to discipline issues in the class.